2020
DOI: 10.1159/000510507
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate of Geographic Atrophy Secondary to Age-Related Macular Degeneration: A Meta-Analysis of Natural History Studies and Implications for Designing Future Trials

Abstract: Introduction: There is no effective treatment for geographic atrophy (GA). To help design future GA treatment trials, we conducted a meta-analysis for GA growth rate and its variability in natural history studies. Methods: Literatures were searched up to April 30, 2020. Data were extracted independently by 2 authors and analyzed using random-effects models. Results: The pooled mean GA growth rate was 1.66 mm2/year (SD = 1.27 mm2/year, I2 = 97.0%, p < 0.001) from 23 studies (3,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…4 b). Due to the discovery of the long-term GA progression model, many clinical trials use the square root of GA area as an endpoint to evaluate treatment efficacy 26 , 39 42 , which can increase the statistical power 27 , 43 and linearize the data for standard statistical analysis (e.g., linear mixed model) 32 . However, it is previously unclear if GA in a subset of patients follow a different disease progression model, which can represent a different GA phenotype with a distinct underlying pathophysiological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…4 b). Due to the discovery of the long-term GA progression model, many clinical trials use the square root of GA area as an endpoint to evaluate treatment efficacy 26 , 39 42 , which can increase the statistical power 27 , 43 and linearize the data for standard statistical analysis (e.g., linear mixed model) 32 . However, it is previously unclear if GA in a subset of patients follow a different disease progression model, which can represent a different GA phenotype with a distinct underlying pathophysiological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 23 studies reported the natural progression of GA lesions in untreated eyes to be 1.66 mm 2 /year 21. Results from the Proxima A and B clinical trials reported a growth rate of 2.09 and 1.90 mm 2 /year, respectively, over the first 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients with bilateral drusen who were examined annually, the location of incident GA was parafoveal (250–1500 µm) in 61.4%, ≤ 250 µm from the foveal center in 17.5%, and subfoveal in 20.2% [ 12 ]. Lesion growth rate varies across studies and individuals and is affected by baseline lesion size (in mm 2 ) [ 13 , 14 ]. In a recent meta-analysis, the pooled mean GA growth rate was shown to be 1.66 mm 2 /year or 0.33 mm/year, and regardless of how GA growth rate was calculated (non-square root transformed, mm 2 ; or square root transformed, mm), a significant association was observed with baseline GA area (mm 2 ) [ 13 ].…”
Section: Disease Progression and Visual Functionmentioning
confidence: 99%
“…Lesion growth rate varies across studies and individuals and is affected by baseline lesion size (in mm 2 ) [ 13 , 14 ]. In a recent meta-analysis, the pooled mean GA growth rate was shown to be 1.66 mm 2 /year or 0.33 mm/year, and regardless of how GA growth rate was calculated (non-square root transformed, mm 2 ; or square root transformed, mm), a significant association was observed with baseline GA area (mm 2 ) [ 13 ]. Since baseline GA area is 1 of the factors that affect GA growth, square root transformation methods can be used in clinical trials to minimize the impact of baseline GA size [ 13 ].…”
Section: Disease Progression and Visual Functionmentioning
confidence: 99%